2009
DOI: 10.1186/1471-2156-10-80
|View full text |Cite
|
Sign up to set email alerts
|

Genomic microsatellites identify shared Jewish ancestry intermediate between Middle Eastern and European populations

Abstract: BackgroundGenetic studies have often produced conflicting results on the question of whether distant Jewish populations in different geographic locations share greater genetic similarity to each other or instead, to nearby non-Jewish populations. We perform a genome-wide population-genetic study of Jewish populations, analyzing 678 autosomal microsatellite loci in 78 individuals from four Jewish groups together with similar data on 321 individuals from 12 non-Jewish Middle Eastern and European populations.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
50
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 56 publications
10
50
2
Order By: Relevance
“…Contemporary Jewish communities have been genetically analyzed both from population genetics and medical perspectives by means of uniparental and recombining markers, [10][11][12][13][14][15][16][17] and more recently also through genome-wide approaches. [18][19][20][21][22][23] However, only a few reports have been published on Sephardic and crypto-Jewish descendants.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary Jewish communities have been genetically analyzed both from population genetics and medical perspectives by means of uniparental and recombining markers, [10][11][12][13][14][15][16][17] and more recently also through genome-wide approaches. [18][19][20][21][22][23] However, only a few reports have been published on Sephardic and crypto-Jewish descendants.…”
Section: Introductionmentioning
confidence: 99%
“…Admixture estimates using markers at a few autosomal loci or based on STRUCTURE clustering results have also shown much higher European admixture than reflected in the Y chromosome (13,18,19). Furthermore, recent studies have found no increase in LD at short distances between markers and suggest increased heterozygosity compared with Europeans, concluding that the AJ population is likely an older and larger population that is distinguished by its Middle Eastern origin, rather than the effect of population bottlenecks (20)(21)(22).To better understand the genome-wide genetic structure of the AJ population and search for genetic signatures of founder events, we genotyped 471 unrelated AJ individuals at 732k autosomal SNPs. Our analysis of this large cohort clarifies many inconsistencies described above, establishing that the AJ population has had substantial admixture with European populations, increasing its genetic diversity and LD, yet maintaining a significant level of founder haplotypes identical-by-descent.…”
mentioning
confidence: 99%
“…This supports the inclusion of Druze individuals (along with Palestinians and Bedouins) in Middle-Eastern reference panels in previous population genetic studies. [35][36][37][38] The data also show, perhaps surprisingly, that Druze communities from different locales are closer to each other than to other Middle-Eastern groups, consistently with the Druze's strict ban on intermarriage. Yet, each of the four communities studied (Galilee, Golan, Carmel, and Lebanon) was genetically distinct, even the more geographically proximate Israeli communities.…”
Section: Discussionmentioning
confidence: 52%